Utilization of Akoontan Application in Preparing Financial Statements at the Public Accounting Firm Heliantono and Rekan : Pemanfaatan Aplikasi Akoontan dalam Penyusunan Laporan Keuangan pada Kantor Akuntan Publik Heliantono dan Rekan - Nur Alimah Ramdhania; Muhammad Yani (International Consortium of Education and Culture Research Studies, 2024)
General Background The rapid development of information technology has fundamentally transformed data management across modern organizations. Specific Background Within public accounting firms, preparing company records requires high precision, yet entities like Heliantono and Rekan Public Accounting Firm still rely on manual processing despite adopting specific applications. Knowledge Gap Lengthy manual transcriptions of bank records and single-entry recording systems cause severe operational inefficiencies, resource waste, and high vulnerability to human mistakes during reporting. Aims This study attempts to apply targeted technological tools to accelerate data processing and minimize recording mistakes. Results The implementation of optical character recognition through the Notebloc Scanner significantly accelerates the conversion of printed bank records into editable digital spreadsheets, minimizing human mistakes. Furthermore, transitioning from a single-entry to a dual-entry recording system provides detailed, consistent, and highly precise documentation. Novelty This application demonstrates the practical synergy of mobile scanning technology and dual-entry principles to resolve specific data bottlenecks within established software environments. Implications Integrating automated extraction with structured recording methods saves time, reduces operational costs, and ensures highly reliable reporting. Highlights: Optical character recognition technology accelerates information extraction from printed bank records. Transitioning from single recording methods ensures consistent and reliable transactional documentation. Automated conversion minimizes human mistakes and reduces operational resource waste. Keywords: Information Technology, Dual Recording System, Data Processing, Accounting Application, Optical Character Recognition